n → ∞ lim ∫ 0 1 ( x n + ( 1 − x ) n ) n 1 d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For finite (and convergent) continuous functions on a finite interval, we can always swap the limit and integral (special case of Lebesque's theorem).
Let's evaluate lim n ( x n + ( 1 − x ) n ) 1 / n . Due to symmetry, we only need to compute the limit and its integral for x > 1 / 2 and multiply the result by 2.
( x n + ( 1 − x ) n ) 1 / n = x ( 1 + ( x 1 − 1 ) n ) 1 / n = x exp ( n 1 ln ( 1 + ( x 1 − 1 ) n ) ) ; for 1 > x > 1 / 2 , 0 < x 1 − 1 < 1 , so for sufficiently large n , the term ( x 1 − 1 ) n in the logarithm will be approaching 0 and we can replace the logarithm by the first (linear) term in its Taylor series: ( x n + ( 1 − x ) n ) 1 / n ≈ x exp ( n 1 ( x 1 − 1 ) n ) .
Clearly, n a n → 0 for ∣ a ∣ < 1 , so we have found the limit to be x in case x > 1 / 2 (and therefore 1 − x for x < 1 / 2 ).
All that's left is computing 2 ∫ 1 / 2 1 x d x = 4 3 .
Due to symmetry, we can compute it for 0 < x < 0 . 5 and multiply the result by two. Then, because x n < < 1 and lim m → ∞ ( 1 + a x ) m = 1 + a m x , 2 ∫ 0 0 . 5 ( x n + ( 1 − x ) n ) 1 / n d x = 2 ∫ 0 0 . 5 ( 1 − n x ) 1 / n d x = 2 ∫ 0 0 . 5 ( 1 − x ) d x = 0 . 7 5 .
This solution is incorrect as it does not properly deal with values about x = 0 . 5 .
You effectively neutralized n with 1/ n at first. Therefore you obtained 0.75 as answer.
Isn't ( 1 + x ) n aprox. 1 + x n valid only when ∣ x ∣ n < < 1 ?
Problem Loading...
Note Loading...
Set Loading...
We can use the fact that ( a n + b n ) 1 / n ⟶ n → ∞ max ( a , b ) . Then the the functional sequence { ( x n + ( 1 − x ) n ) 1 / n } n converges simply to max { x , 1 − x } then by the dominated convergence theorem (the integrand is clearly dominated) the limit is ∫ 0 1 max { x , 1 − x } d x = 4 3